DEVELOPMENT AND VALIDATION OF QUALITY OF LIFE QUESTIONNAIRE IN INFANTILE ESOTROPIA: PARENTS VERSION - Waheeda-Azwa, Hussein; Hassan , Norul Badriah; Abdullah , Sarimah; Che Hamzah , Jemaima; Shatriah, Ismail (International Journal of Allied Health Sciences, 2021)
Background: Infantile esotropia is a common strabismus problem in Malaysia. Parents of children with infantile esotropia reported various concern affecting their quality of life. However, there is no specific tool to measure their quality of life in our native language. The objective of this study is to develop and validate new quality of life questionnaire in parents of children with infantile esotropia. Methodology: The study was conducted from 2016 to 2019. The questionnaire was developed based on literature review, survey, interview and brainstorming with experts. A validation study was conducted on the parents of children with infantile esotropia. Results: A total of 101 proxy/parents were recruited. A new questionnaire in Bahasa Malaysia for parents (4 subthemes, 25 items) was developed. All items in the questionnaire had satisfactory content evidence (scale level-content validity index, averaging method > 0.8), and good response process evidence (scale-level face validity index, averaging method >0.8). The questionnaire was found to have high internal consistency (Cronbach’s alpha: 0.85-0.89 (proxy/parent); acceptable intraclass correlation coefficients (r=0.746, p<0.01(proxy/parents); and significant correlations with the Intermittent Exotropia Questionnaire (r=0.444, p<0.01 (proxy/parent). Conclusion: A new valid and reliable quality of life questionnaire for parents of children with infantile esotropia has been developed. The questionnaire provides useful information on the actual problems from the parents’ own perspectives, thus helpful in the strabismus management and clinical decision. Keywords: infantile esotropia, quality of life, questionnaire